1996
DOI: 10.1042/bj3170013
|View full text |Cite
|
Sign up to set email alerts
|

Research communication copper-1,10-phenanthroline induces internucleosomal DNA fragmentation in HepG2 cells, resulting from direct oxidation by the hydroxyl radical

Abstract: In view of the current speculation regarding the possible role of reactive oxygen species (ROS) in apoptosis, both under physiological conditions and in response to chemicals that promote their intracellular formation, the present investigation was undertaken to examine whether DNA fragmentation during oxidative stress results from endonuclease activity (apoptosis) or from direct attack by ROS. We report that the incubation of HepG2 cells (a human-derived hepatoma cell line) with the copper(II) complex of 1,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 28 publications
4
55
0
Order By: Relevance
“…3A) and nucleosome mapping using an alternative method based on DNA digestion by a chemical agent (phenanthroline) in human Raji B-cells (Supplemental Fig. 3C; Tsang et al 1996). In both cases, we confirmed a correlation between nucleosome depletion and CGI length; we also sequenced sonicated genomic DNA that showed only very little sequencing bias in the promoters containing the largest CpG content (Supplemental Fig.…”
Section: Gc Content and Cgis Define Nucleosome Depletion Patterns At supporting
confidence: 57%
See 1 more Smart Citation
“…3A) and nucleosome mapping using an alternative method based on DNA digestion by a chemical agent (phenanthroline) in human Raji B-cells (Supplemental Fig. 3C; Tsang et al 1996). In both cases, we confirmed a correlation between nucleosome depletion and CGI length; we also sequenced sonicated genomic DNA that showed only very little sequencing bias in the promoters containing the largest CpG content (Supplemental Fig.…”
Section: Gc Content and Cgis Define Nucleosome Depletion Patterns At supporting
confidence: 57%
“…The sequencing procedure was conducted using at least 1 ng of starting material and run on a Genome Analyzer II (Illumina). The in vivo phenanthroline digestion of nucleosomes was adapted from Tsang et al (1996) and is described in the Supplemental Methods together with the computational processing and analysis pipeline.…”
Section: Chip-seq and Mnase-seqmentioning
confidence: 99%
“…Extracellular addition of hydrogen peroxide could induce apoptosis and necrosis, and Z-DEVD-CH 2 F inhibited hydrogen peroxide-induced cell death (data not shown), indicating that hydrogen peroxide can induce cell death. Tsang et al reported that hydroxyl radical can induce internucleosomal DNA fragmentation even at 48C and proposed that hydroxyl radical directly aected DNA to induce DNA fragmentation (Tsang et al, 1996). It is still possible that direct oxidation of DNA by hydroxyl radical might synergistically work with the caspase 3-like protease to induce DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that nucleic acid oxidation occurs widely in vulnerable neuronal populations in AD (6) and oxidative damage can directly cause DNA fragmentation (7). Therefore, DNA damage possibly resulting from oxidative stress involves vulnerable neurons in AD beyond the distribution of amyloid deposition or neurofibrillary tangles, which may be related to neuronal cell death occurring independently of the classical AD pathology (3).…”
mentioning
confidence: 99%